Cancer incidence in the Swedish leather tanning industry: updated findings 1958–99 - Mikoczy, Z (BMJ Group, 2005)
Aims: To assess how a 10 year extension of the follow up period affected cancer incidence in the Swedish leather tanning cohort. Methods: A cohort of 2027 tannery workers (of which 482 were women) who had been employed for at least one year between 1900 and 1989 at one of three Swedish leather tanneries, was established. The start of observation varied between 1958 and 1966 for the three plants. Through linkage with the Swedish Cancer Registry, incident cancer cases were recorded up to 1999. Cause specific expected cancer incidence was calculated for 1958–99 based on calendar year, sex, and five year age group specific incidence rates for the counties where the plants had been located. Altogether 56 022 person-years at risk were generated. Results: A total of 351 incident cancer cases were observed compared to 302 expected, which resulted in an increased standardised incidence ratio (SIR) of 1.16 (95% CI 1.04 to 1.29). An enhanced risk for prostate cancer was observed (SIR 1.44, 95% CI 1.10 to 1.86), mainly attributable to the later part of the observation period (1990–99). In this updated analysis the previously observed risk excess for soft tissue sarcomas was no longer significant (SIR 2.62, 95% CI 0.96 to 5.70). For multiple myelomas and sinonasal cancer the slight non-significant excesses remained, still based on very few cases. Conclusions: The increased risk for prostate cancer in the present study might be a chance finding, but is noteworthy, since it is in acccordance with the finding of increased SIR for prostate cancer among leather workers in another recent Swedish study. Moreover, excess risks for prostate cancer among farmers have been reported, indicating pesticides as possible causative agents. Leather tanners have also been exposed to pesticides.